The peripheral hemodynamics of the lower extremities of powerlifters - O. V. Kalabin; A. P. Spitsin (Спортивная медицина: наука и практика, 2020)
Objective: to study the features of peripheral hemodynamics of the lower extremities of powerlifters depending on their experience and qualification. Materials and methods: the study of cardiovascular systemwas conducted in 38 men aged from 18 to 25 years engaged in powerlifting. 20 participants had sports categories (1-3) and 18 participantswere candidates or masters of sports. To study the regional blood flow in the areas of «foot», «calf» and «hip» the hardware and software complex «Reo-Spectrum-3» of «Neuro-Soft» were used. Results: significant decrease in the amplitude of the systolic wave, the arterial wave, the maximum systolic value of the venous component of the hip of powerlifters was revealed in comparison with the control group. A significant decrease in the amplitude-frequency index of powerlifters was also revealed. The index of fast filling was significantly lower in powerlifters. The values of the «inflow-outflow»ratio pointed at the change of the tonus of vessel wall in powerlifters. The average speed of slow filling indicated a decrease in the tonus of small and medium arteries in powerlifters. The change in vascular tone in powerlifters indirectly indicated a shift in the autonomic balance towards the predominance of sympathetic influences.All parameters showed an increased stress of the mechanisms of regulation of cardiac activity. Conclusions: the nature of blood circulation shifts includes changes in both the arterial and venous parts of the blood stream. The most pronounced changes in peripheral blood circulation were found in the areas of «calf» and «foot». With the growth of sports skills, the nature and degree of vascular changes increases, which indicates a decrease in the adaptive capacity of the vascular system of the lower extremities to intense physical activity.